Gambaran penerapan tanggapan darurat kebakaran di Kantor Desa Bukit Raya - Suheriah Mulia Devi; Miyanda Putri Siswanto (Abdimas Siliwangi, 2024)
Fires in the workplace cause quite serious damage, both in terms of material and loss of life. A fire emergency response system in the workplace is very important and needs to be implemented to minimize the potential hazards and risks of fire in the workplace. This study aims to provide an overview of the Implementation of the Fire Emergency Response System at the Bukit Raya Village Office. This study used a qualitative research method by collecting data through interviews with 2 informants consisting of the village secretary and village staff, Bukit Raya village. The results of this study indicate that there is no emergency response system policy in the Bukit Raya village office such as a passive fire protection system and an inadequate active protection system and there is no formation of an emergency response team, evacuation route facilities, evacuation route directions, gathering points and no inspection and maintenance of the active protection system in the form of APAR in the Bukit Raya village office.